More nuts, more squirrels, more damage? The covariation of beech (Fagus sylvatica) masting with grey squirrel (Sciurus carolinensis) abundance, and bark stripping damage, in the UK - Eleanor R. Scopes; Robin Gill; Cally Ham (European Journal of Wildlife Research, 2026)
Grey squirrels ( Sciurus carolinensis ) are an invasive non-native species in the UK which can strip bark from trees, detrimentally impacting biodiversity and forestry. Extensive control measures are undertaken to reduce grey squirrel populations each year; however, it is unclear if abundance influences the extent of damage. Predicting changes in abundance could be an important technique to increase the efficacy of control measures. We explore whether climate-based predictors of beech ( Fagus sylvatica ) masting, covary with an abundance index of grey squirrels. We find predicted masting years covary with the abundance of grey squirrels at all sites and those in broadleaf woodland the following year. We also find that predicted masting years covary with squirrel abundance at beech dominated sites in the same year as masting. These inconsistent patterns may be due to the limitations with the proxies used this analysis, but indicate potential hypotheses for future studies. We also investigate whether grey squirrel abundance index covaries with the prevalence of accumulated bark stripping damage with inconclusive results. More research is needed to identify the drivers of bark stripping to identify new preventative measures. Our exploratory results suggest potential influences of beech masting on grey squirrel abundance, although more research is needed before this could be used within management.